2022
DOI: 10.20408/jti.2022.0017
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of missed injuries in patients with severe trauma

Abstract: Purpose:To analyze the data of trauma patients with undetected injuries at the time of initial resuscitation during the primary and secondary surveys. Methods: We retrospectively reviewed the medical records of 807 patients who were hospitalized at the National Trauma Center, Seoul, Korea from June 1, 2019 to June 30, 2021. Results: In trauma patients with an Injury Severity Score ≥16 accounted for 27.5% in the non-missed injury group (non-MIG), but this rate was considerably higher at 71.2% in MIG. The mean h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…In this study, the detection rate of type-I DDIs was 3.1% (n=12), of which four patients had clinically significant missed injuries (CSMI). TTS was strictly carried out at 24 hours in seven (47%) of the studies on 10399 patients, Figure 2 [ 5 , 10 , 13 , 15 , 21 , 24 , 26 ]. Five of the studies reported type-I DDI in terms of the number of patients, with a detection rate of 1.9% in 10193 patients [ 5 , 10 , 13 , 15 , 24 ], while one reported type-I DDIs as 173 injuries at a detection rate of 56% [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the detection rate of type-I DDIs was 3.1% (n=12), of which four patients had clinically significant missed injuries (CSMI). TTS was strictly carried out at 24 hours in seven (47%) of the studies on 10399 patients, Figure 2 [ 5 , 10 , 13 , 15 , 21 , 24 , 26 ]. Five of the studies reported type-I DDI in terms of the number of patients, with a detection rate of 1.9% in 10193 patients [ 5 , 10 , 13 , 15 , 24 ], while one reported type-I DDIs as 173 injuries at a detection rate of 56% [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…TTS was strictly carried out at 24 hours in seven (47%) of the studies on 10399 patients, Figure 2 [ 5 , 10 , 13 , 15 , 21 , 24 , 26 ]. Five of the studies reported type-I DDI in terms of the number of patients, with a detection rate of 1.9% in 10193 patients [ 5 , 10 , 13 , 15 , 24 ], while one reported type-I DDIs as 173 injuries at a detection rate of 56% [ 26 ]. Due to heterogeneity in methodology and outcome assessment, comprehensive statistical analysis is not possible (Figure 3 ).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations